Exploring mathematics teachers' instructional and formative assessment practices for fostering 21st-century skills acquisition among secondary school students in Tanzania - George Mathias; Thabita Lupeja; Emmanuel Deogratias (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
Strengthening the development of 21st-century skills in rural secondary schools remains an urgent educational priority, prompting this study to examine how mathematics teachers enact instructional and formative assessment practices to support these competencies. This qualitative research investigates how mathematics teachers in Kwimba district, Tanzania, design and implement pedagogical and assessment strategies to cultivate critical thinking, creativity, collaboration, communication, problem-solving, and digital literacy. Data were collected from ten mathematics teachers across ten public ordinary-level secondary schools through semi-structured interviews, classroom observations, and documentary reviews. Thematic analysis was applied to identify recurring patterns in instructional and assessment practices. Findings show that while teachers exhibit moderate competence in promoting critical thinking and problem-solving, their capacity to enhance creativity, collaboration, communication, and digital literacy remains limited. Structural constraints—including overcrowded classrooms, insufficient training, and limited resources—restrict the effective use of student-centered instruction and formative assessment. The study recommends targeted professional development, improved access to instructional materials, and greater curricular flexibility to strengthen teachers’ ability to foster 21st-century competencies. The study contributes novel empirical insights into the instructional–assessment nexus in under-resourced rural contexts, offering evidence to inform policy and teacher-capacity reforms.